Productive Thinking Skills Included in Art Education Text Books for the Primary Stage - Al-Khasawneh, Hana Mohammed; Al-Qarra’a, Ahmed Odeh (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to know the productive thinking skills contained in art education books for the basic stage in Jordan. The researcher followed the descriptive analytical approach using a content analysis card prepared for this purpose. It included nine productive thinking skills: originality, fluency, flexibility, inference, interpretation, and knowledge of assumptions, deduction, evaluating arguments and solving problems, with a total 27 sub-skills. The validity of the study tool and stability of analysis confirmed. The results showed that the productive thinking skills in books was 5546 repeated, and in the eighth grade student book were the highest with a percentage of 35.7%. In sequence, the skill of evaluating arguments was 25%, the skill of solving problems 17%, the skill of deduction 14%, the skill of the conclusion 11%, and each of the interpretation and knowledge of assumptions 8%, the fluency 6%, the flexibility 6%, and the originality 5%. Then the tenth grade student book 30.6%, and the results came as follows: the skill of evaluating arguments 26%, deduction 23%, and solving problems 23%, while originality 2%, fluency 3%, flexibility 2%, inference 9%, interpretation 7%, knowledge of assumptions 6%. The lowest was the ninth grade student book 28.8%, where the percentages according to the following were 26% problem solving skill, 21% evaluating arguments, 17% deduction skill, 8% originality skill, 4% fluency skill, 4% flexibility, 10% inference skill, 8% interpretation, and knowledge of assumptions 4%. Several recommendations and suggestions emerged from the study, the most important of which is the necessity of enriching the art education books for the basic stage of productive thinking skills, especially those that are less available and need to balance them in books.